Teaching Literature in Comprehensive Secondary School Curricula in Serbia (from 1990 to the Present) - Mihajlović, Jelena D. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper provides a diachronic overview of curricula for Serbian Language and Literature courses in secondary schools from 1990, when comprehensive secondary schools were reinstated into the education system of the Republic of Serbia, to present day. The structure and contents of the literary elements were monitored, analyzed, and contrasted. The aim of the curricula analysis in the indicated period is to ascertain and explain the positive and negative aspects of previous reforms to which literary content was exposed, and to, in accordance with the obtained results, draw appropriate conclusions and provide recommendations for their future improvements.
Keywords: education; comprehensive secondary school; curriculum; curriculum structure; teaching literature